Strategy Economic Development Creative Based on BUMDes Change Management: Inclusive Creative Economy Change Management of Panggok Market - Prasetyaningrum, Dina; Hakim, Hakim (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2025)
One thing public organizations cannot escape is organizational transformation. Nevertheless, there is sometimes opposition to the changes that take place rather than positive reception. To improve the economic welfare of the Cilacap community, the Village Owned Enterprise (BUMDES) Slarang Village, Cilacap and other public organizations must plan organizational changes based on community interests. This includes communication with the youth organization of Slarang Village residents and a vision, mission, strategy, and goals. With the participation of citizens and cooperation in human relations, creative economic programs do not cause negative resistance impacts on the environment. This research was conducted using qualitative research analysis tests. Qualitative research is a descriptive research method and uses analysis to explain a phenomenon. Data collected in qualitative research are in the form of written and spoken words, such as ethnography, document studies, natural observations, and phenomenology and are supported by through literature studies of journal publications and books. Research results show that change management is aimed at for give business solutions which required in success in an organized and methodical manner, through managing the impact of change on those involved. As in Panggok Market, it is a culinary tourism that is built focusing on change management of economic development based on creativity has been built with creativity both from its place, its food or the people who sell it. Panggok Market was established with the aim of improving the welfare of the surrounding community in accordance with the vision and mission of Panggok Market and preserving traditional Central Javanese food. Panggok market has inspired other culinary villages that follow the railroad tracks, which have proven to be effective in improving the economy of residents.